PLGA particulate subunit tuberculosis vaccines promote humoral and Th17 responses but do not enhance control of Mycobacterium tuberculosis infection. - Anneliese S Ashhurst; Thaigarajan Parumasivam; John Gar Yan Chan; Leon C W Lin; Manuela Flórido; Nicholas P West; Hak-Kim Chan; Warwick J Britton (PLoS ONE, 2018)
Tuberculosis places a staggering burden on human health globally. The new World Health Organisation End-TB Strategy has highlighted the urgent need for more effective TB vaccines to improve control of the disease. Protein-based subunit vaccines offer potential as safe and effective generators of protective immunity, and the use of particulate vaccine formulation and delivery by the pulmonary route may enhance local immunogenicity. In this study, novel particulate subunit vaccines were developed utilising biodegradable poly(lactic-co-glycolic acid) (PLGA) slow-release particles as carriers for the Mycobacterium tuberculosis lipoprotein MPT83, together with the adjuvants trehalose-dibehenate (TDB) or Monophosphoryl lipid A (MPL). Following delivery by the pulmonary or subcutaneous routes, the immunogenicity and protective efficacy of these vaccines were assessed in a murine model of M. tuberculosis infection. When delivered peripherally, these vaccines induced modest, antigen-specific Th1 and Th17 responses, but strong anti-MPT83 antibody responses. Mucosal delivery of the PLGA(MPT83) vaccine, with or without TDB, increased antigen-specific Th17 responses in the lungs, however, PLGA-encapsulated vaccines did not provide protection against M. tuberculosis challenge. By contrast, peripheral delivery of DDA liposomes containing MPT83 and TDB or MPL, stimulated both Th1 and Th17 responses and generated protection against M. tuberculosis challenge. Therefore, PLGA-formulated vaccines primarily stimulate strong humoral immunity, or Th17 responses if used mucosally, and may be a suitable carrier for vaccines against extracellular pathogens. This study emphasises the critical nature of the vaccine carrier, adjuvant and route of delivery for optimising vaccine efficacy against TB.